Clinical Outcomes and Adverse Events of Gastric Endoscopic Submucosal Dissection of the Mid to Upper Stomach under General Anesthesia and Monitored Anesthetic Care - Jong-In Chang; Tae Jun Kim; Na Young Hwang; Insuk Sohn; Yang Won Min; Hyuk Lee; Byung-Hoon Min; Jun Haeng Lee; Poong-Lyul Rhee; Jae J Kim (Clinical Endoscopy, 2022)
Background/Aims Endoscopic submucosal dissection (ESD) of gastric tumors in the mid-to-upper stomach is a technically challenging procedure. This study compared the therapeutic outcomes and adverse events of ESD of tumors in the mid-to-upper stomach performed under general anesthesia (GA) or monitored anesthesia care (MAC). Methods Between 2012 and 2018, 674 patients underwent ESD for gastric tumors in the midbody, high body, fundus, or cardia (100 patients received GA; 574 received MAC). The outcomes of the propensity score (PS)-matched (1:1) patients receiving either GA or MAC were analyzed. Results The PS matching identified 94 patients who received GA and 94 patients who received MAC. Both groups showed high rates ofen bloc resection (GA, 95.7%; MAC, 97.9%; p=0.68) and complete resection (GA, 81.9%; MAC, 84.0%; p=0.14). There were no significant differences between the rates of adverse events (GA, 16.0%; MAC, 8.5%; p=0.18) in the anesthetic groups. Logistic regression analysis indicated that the method of anesthesia did not affect the rates of complete resection or adverse events. Conclusions ESD of tumors in the mid-to-upper stomach at our high-volume center had good outcomes, regardless of the method of anesthesia. Our results demonstrate no differences between the efficacies and safety of ESD performed under MAC and GA.